Comparison of two methods for alveolar bone loss measurement in an experimental periodontal disease model in rats - Diego Nique Liberman; Roberta Manjabosco Pilau; Lorena Floriani Orlandini; Eduardo José Gaio; Cassiano Kuchenbecker Rösing (Sociedade Brasileira de Pesquisa Odontológica, 2011)
There are many studies that evaluate possible risk factors for periodontal diseases in animals. Most of them have focused only on the biological aspects of disease occurrence; therefore, it has been difficult to compare studies of the different methodological approaches. The aim of the present study was to compare different methods - linear and area - of the evaluation of morphometrical alveolar bone loss. Sixty hemimaxillae, defleshed and stained with 1% methylene blue to delineate the cementoenamel junction and alveolar bone crest, were obtained from a previous study that induced periodontal disease by means of ligatures in two groups of fifteen Wistar rats during 9 weeks. Ligatures were placed around the right upper second molars, and the contra-lateral teeth remained as intra-group controls. Digital photographs were taken from the specimens and submitted to a single, calibrated, blind examiner who performed the morphometrical evaluation of alveolar bone loss using both linear and area methods. Mean values of linear and area measurements were obtained from each side - buccal and palatal - of the specimens. The degree of association between the two methods was determined by Pearson's Correlation Coefficient. An almost perfect association (0.98) was determined between the linear and area evaluations. A mathematical formula was subsequently created to estimate the total area of alveolar bone loss, from linear mean measurements. Both methods were suitable for detecting bone level alterations. The results of the present study allow for the transformation of data and better compilation of results from different studies.